Infrastructures and planning in Naples in nineteenth century - Rossi, Pasquale (TeMA - Journal of Land Use, Mobility and Environment, 2011)
Naples in the middle of nineteenth century is a “construction site” for industrial and residential development at the same of other great towns (London, Paris, Wien) that realized interventions in Europe. During the reign of Ferdinando II di Borbone (1830-59) were realized a project that previded for an industrial quarter at east and a residential part in the western city, and in the territory constructions provincial roads, bridge connection (Garigliano and Calore rivers), infrastructures and railways (Napoli-Portici, 1839). After “Unit of Italy” (1861) same architects and engineers (Luigi Giura, Errico Alvino, Antonio Francesconi, Gaetano Genovese and others) that work in preceding regime will continue to project of construction city stand guarantor for the operational continuity. In the second half of nineteenth century there will be many problems for to realize projects and planning until 1884 when begin special “Risanamento plan” after epidemic cholera problem. In the 1887 the Municipality of Naples define a particulary plan of a “Industrial District” that will be not realized in the same area that in the present wait for solution one more time.